1990
DOI: 10.1007/bf02764298
|View full text |Cite
|
Sign up to set email alerts
|

HLA DR and DQ expression on human retinal pigment epithelial cells in vitro

Abstract: In a previous immunohistopathological study, we demonstrated a deviant expression of class II antigens on the uveal pigment epithelial cells of patients with proliferative diabetic retinopathy. The mechanisms triggering this abnormal expression by epithelial cells are not well known, and we tried to induce this phenomenon on primary cultures of human retinal pigment epithelial (RPE) cells. Confluent RPE-cell monolayers were supplemented with several biological or chemical reagents [recombinant interferon gamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Such data favoured the hypothesis of an eventual role of immu nologic phenomena occuring in ocular pro liferative diseases and mediating their devel opment. Peptide growth factors such as EGF and FGF have been found to regulate and stimulate the production of gamma inter feron [27], a potent inducer of class II anti gen expression in different cells, both in vivo [28] and in vitro [29,30], The presence in preretinal membranes of great amounts of FGF and EGF, possibly released or synthe sized by the damaged ischemic or detached retina, may thus induce interferon-dependent HLA DR and DQ expression by prolif erative cells, leading to an immune reaction, as suggested by Bottazzo et al [31], and maybe enhancing the proliferative process.…”
Section: Discussionmentioning
confidence: 99%
“…Such data favoured the hypothesis of an eventual role of immu nologic phenomena occuring in ocular pro liferative diseases and mediating their devel opment. Peptide growth factors such as EGF and FGF have been found to regulate and stimulate the production of gamma inter feron [27], a potent inducer of class II anti gen expression in different cells, both in vivo [28] and in vitro [29,30], The presence in preretinal membranes of great amounts of FGF and EGF, possibly released or synthe sized by the damaged ischemic or detached retina, may thus induce interferon-dependent HLA DR and DQ expression by prolif erative cells, leading to an immune reaction, as suggested by Bottazzo et al [31], and maybe enhancing the proliferative process.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Forrester's group [Liversidge et al, 1988] and Zavazava et al [1991] published the expression of not only MHC class I but also of MHC class II on RPE cells in vitro after stimulation with or without lymphokines. During the past 10 years, more articles dealing with MHC expression, a marker of the antigen-presenting ability of cells [Baudouin et al, 1990] and with lymphocyte activation by RPE cells [Osusky et al, 1997] have been published and have demonstrated the increased interest in the immunological characteristics of these cells. Additionally, an in vitro study performed by Percopo et al [1990] reveals a strong immunological activation through RPE cells via T-lymphocyte proliferation and IL-2 secretion.…”
Section: In Vitro Studiesmentioning
confidence: 99%